2016
DOI: 10.5588/ijtld.15.1007
|View full text |Cite
|
Sign up to set email alerts
|

<I>SLCO1B1</I> gene polymorphisms do not influence plasma rifampicin concentrations in a South Indian population

Abstract: This is the first study to show that rs11045819, rs4149032 and rs4149033 polymorphisms in the SLCO1B1 gene did not influence RMP concentrations in Indian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…Much interest in Europe has focused on the role of rs4149056 (521T>C, *5) in toxicity of statin therapy (27), while studies in South Africa and Uganda have implicated two SLCO1B1 SNPs (rs4149032 and rs11045819) in reduced RIF exposure (1820). However, in keeping with a recent report from southern India (21), inclusion of these genotypes did not significantly improve the PK model fit for RIF in our study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Much interest in Europe has focused on the role of rs4149056 (521T>C, *5) in toxicity of statin therapy (27), while studies in South Africa and Uganda have implicated two SLCO1B1 SNPs (rs4149032 and rs11045819) in reduced RIF exposure (1820). However, in keeping with a recent report from southern India (21), inclusion of these genotypes did not significantly improve the PK model fit for RIF in our study.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, while rs11045819 is believed to be functional (463C>A, *4), rs4149032 is an intronic SNP of unclear functional status which, in European populations, is in strong linkage disequilibrium with rs11045819 (28). However, these SNPs had a low level of linkage disequilibrium (D′ 0.16) in Malawi, echoing findings from South Africa (18) and southern India (21). There are large differences in linkage disequilibrium worldwide and within Africa (15), so it is possible that previously recognized SNPs may tag functional genes in some populations but not others.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We undertook substudies in the same population to examine the influence of polymorphisms in the NAT2 and SLCO genes on plasma INH and RMP concentrations, respectively. While the NAT2 genotypes significantly impacted INH levels, the SLCO genotypes (rs11045819, rs4149032, and rs4149033) did not influence RMP concentrations (18,19). In this study, we undertook NAT2 genotyping in only about a third of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies showed that it did not influence the exposure and involves genetic variability 11,12 while presently there are no studies of the major SNPs in Indonesian patients. This study aimed to determine the major SNPs which may influence efficacy of treatment among Indonesian PTB and EPTB patients and the second objective of the study was to evaluate their potential impact on the clinical outcome.…”
Section: C463amentioning
confidence: 99%